Influence of dietary genistein and polyunsaturated fatty acids on lipid peroxidation and fatty acid composition of meat in quail exposed to heat stress - Orhan, Cemal; Şahin, Nurhan; Şahin, Kazım; Küçük, Ömersman (Springer, 2021)
This experiment was conducted to investigate the effects of polyunsaturated fatty acids (PUFA) and genistein on performance and meat fatty acid profiles in quail exposed to heat stress. A total of 360 Japanese quail were divided into 12 groups in a 2 x 2 x 3 factorial design; each group comprised 30 quail with five replicates and were kept either at 22 +/- 2 degrees C for 24 h/day (Thermoneutral, TN) or 34 +/- 2 degrees C for 8 h/day (08:00 to 17:00 h) followed by 22 degrees C for 16 h (heat stress, HS) conditions. The diet contained either two levels of PUFA at 15 or 45% of total fat or three levels of genistein at 0, 400, or 800 mg/kg. Bodyweight gain, feed intake, and feed efficiency were lower (p >= 0.01) for quail reared under heat stress and fed low PUFA. Increasing dietary genistein in a linear manner improved the productive performance (p < 0.001). Heat stress caused increases in serum and thigh meat malondialdehyde (MDA) concentrations and decreases in genistein and vitamin E and A concentrations in serum and thigh meat (p < 0.001). High PUFA (PUFA45) in the diet of quail caused greater 18:2, 18:3 ALA, EPA, DHA, n-6, and n-3 PUFA as well as total PUFA and total USFA percentages (p < 0.001) in the thigh muscle, some of which decreased with heat stress (p >= 0.006) with no regard to genistein supplementation. This study revealed that genistein with greater doses along with greater PUFA inclusion to the diet of quail reared under heat stress is recommended for alleviating adverse effects of heat stress and for yielding healthier meat for human consumption.
Keywords: Heat stress; Genistein; Polyunsaturated fatty acids; Lipid oxidation; Quail